Construction and characteristic analysis of the cultural genes map of Grand Canal bridge facilities: a case study in Hangzhou section, China - Wenting Wu; Shuming Jin; Shanfeng Zhang; Yi Mei; Kai Zhou (Journal of Asian Architecture and Building Engineering)
Taking the representative bridge facilities of the Hangzhou section of the Grand Canal as an example, uses the reverse transcription extraction method to refine cultural elements information, and classifies and analyzes to obtain the cultural gene identification framework of the Grand Canal bridge facilities. Based on this, various types of cultural genes are encoded according to the principle of cultural gene classification, in order to clarify the four major types of cultural genes: main genes, accessory genes, hybrid genes, and variant genes, forming a cultural gene encoding sequence map and analyzing their basic characteristics. The results show: 1) a cultural gene identification framework for the cultural genes of the Grand Canal bridge facilities composed of 6 gene categories, 8 identification factors, and 17 identification indicators has been established. 2) Accessory genes account for the largest proportion in the four major categories of cultural genes, followed by main genes, and the proportions of mixed genes and variant genes are the same. 3) The genetic features, functional positioning, and value inheritance paths contained in each type of cultural gene are different. The research results provide new ideas for the scientific protection and inheritance of the cultural heritage of the Grand Canal.